2018
DOI: 10.1140/epjc/s10052-018-5729-9
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index in generalized superconductors with Born–Infeld electrodynamics

Abstract: We investigate, in the probe limit, the negative refraction in the generalized superconductors with the BornInfeld electrodynamics. We observe that the system has a negative Depine-Lakhtakia index in the superconducting phase at small frequencies and the greater the Born-Infeld corrections the larger the range of frequencies or the range of temperatures for which the negative refraction occurs. Furthermore, we find that the tunable Born-Infeld parameter can be used to improve the propagation of light in the ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 90 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Meanwhile, we find that the effect of the C 2 F 2 correction on the superconductor phase transition is similar to the one of the Weyl correction(C F 2 ) on the superconductor model in Ref. [67] but in contrast to the influence of the pure high curvature correction [33][34][35][36] or the nonlinear electrodynamics [33,34,[37][38][39] on the superconductor model.…”
Section: Numerical Partmentioning
confidence: 81%
See 1 more Smart Citation
“…Meanwhile, we find that the effect of the C 2 F 2 correction on the superconductor phase transition is similar to the one of the Weyl correction(C F 2 ) on the superconductor model in Ref. [67] but in contrast to the influence of the pure high curvature correction [33][34][35][36] or the nonlinear electrodynamics [33,34,[37][38][39] on the superconductor model.…”
Section: Numerical Partmentioning
confidence: 81%
“…On the other hand, in order to understand the influences of the 1 λ (λ is the 't Hooft coupling) corrections on the holographic superconductor models, many works took into account the high curvature correction [33][34][35][36] and nonlinear electrodynamics [36], such as the Born-Infeld term [21,37,38], the Power-Maxwell term [33,34], Logarithmic term [39] and exponential term [40]. The results showed that both high curvature correction and nonlinear electrodynamics parameters hinder the conductor/superconductor phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that Mahapatra et al [23] constructed the generalized holographic superconductors via the Stückelberg mechanism [24][25][26] in the four dimensional R-charged black hole and observed that the superconducting phase can exhibit a negative Depine-Lakhtakia (DL) index [27] at low frequencies and below a cut-off value of the charge parameter even in the probe limit. Extending the investigation to the generalized superconductors with Born-Infeld electrodynamics, Cheng et al found that the system has a negative DL index in the superconducting phase at small frequencies and the greater the Born-Infeld corrections the larger the range of frequencies or the range of temperatures for which the negative refraction occurs [28]. The refractive index in the holographic dual models can also be found, for example, in Refs.…”
Section: Introductionmentioning
confidence: 95%
“…In order to compare with the results given in Refs. [23,28], we will concentrate on the cases for the model parameters ξ = 0.2 and ξ = 0.5 in our discussion. For the convenience of numerics, we will set c 1 = r h and c 2 = −r 2 h /2, and choose the range of graviton mass parameters 0 ≤ m ≤ 1.2, just as in [11].…”
Section: Scalar Condensation and Phase Transitionmentioning
confidence: 99%
“…Another effect expected is the Casimir-like force which arises from the quadrupole moments induced by quantum gravitational vacuum fluctuations [6][7][8][9][10][11][12][13], in close analogy to the Casimir and the Casimir-Polder forces [14,15]. Furthermore, quantum fluctuations of spacetime may serve as an environment that provides indirect interactions between the two independent gravitationally polarizable subsystems, which may lead to entanglement generation [16].…”
Section: Introductionmentioning
confidence: 99%